PENGARUH IKLAN, PROMOSI PENJUALAN, HUBUNGAN MASYARAKAT, PENJUALAN PERSONAL DAN PEMASARAN LANGSUNG TERHADAP EKUITAS MEREK INDOMARET (STUDI KASUS MASYARAKAT INDOMARET DI KOTA BOGOR) - Eko; Siti Kartikawati (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
Indomaret is a minimarket network in Indonesia that has a franchise system. Indomaret is a network minimarkets that provide a wide range of basic necessities and daily necessities. Indomaret has a slogan that is â€œEasy and Economicalâ€. This type of research is data collection methods using a questionnaire. The data analysis model which was used is multiple linear regression analysis. The sample selection was done by purposive and insidential. The sample amounted to 100 respondents. Adjusted R Square results shows that 59,5% of brand equity factors can be explained by advertising, sales promotion, public relations, personal sales, and direct marketing while the remaining 40,5% is explained by other factor which was not examined in this study. While the F test result show that simultaneously the variables of advertising,sales promotion, public relations, personal selling, and direct marketing simultaneously have a positive and significant effect on brand equity with the result of the analysis namely the value of Fcount (30,030) > Ftable (2,310). The result of the t test shows that the advertising direct marketing variables has a positive and significant effect on brand equity in the Indomaret Minimarket in Bogor. The sales promotion variables, public relations, and personal sales partially did not have a positive and significance. The dominant variable effecting brand equity of Indomaret in Bogor is direct marketing.